Morphological analysis of particles in transmission electron microscopy image using image processing - Phankokkruad, Manop; Sirirat, Wacharawichanant (My University, 2013)
The analysis of material particles in the transmission electron microscopy (TEM) image is the most important in the development and synthesis of the new materials for application in many fields. Manual identification is the hard work, spent a lot of time and inaccurate method. To solve this problem, the image processing is proposed for automatically identifies the material particles boundary and size in TEM images in or order to extract the useful data. The image processing method has been experimented on variety of TEM images and very promising results have been achieved given more accuracy. Experimental results show that the proposed method gave the high adaptability, more accurate and rapidly than the manual method. © (2013) Trans Tech Publications, Switzerland.
Keywords: Image processing; Materials; Morphology; Transmission electron microscopy